Changes in the number of macrophage and lymphocyte cells in chronic periodontitis due to dental X-ray exposure - Alhidayati Asymal; Eha Renwi Astuti; Rini Devijanti (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Periodontitis is an inflammatory disease caused by specific microorganisms that attacks tooth-supporting tissues, P. gingivalis bacteria are mostly found in patients suffering from chronic periodontitis which is usually diagnosed by means of clinical and radiographic examination. The latter play important roles in the management of periodontitis, including: establishing diagnosis, determining treatment plans and evaluating the results of treatment. Unfortunately, the use of X-rays to perform such radiographic examination has negative effects since the body’s various parts, especially the head, are not well protected from the effects of X-ray radiation. Purpose: This research aimed to analyze the effects of dental X-ray exposure on the number of macrophages and lymphocytes in experimental subjects suffering from periodontitis. Methods: 36 rats that had been diagnosed with chronic periodontitis were divided into three groups, namely: a control group, treatment group I (exposed to a 0.16 mSv dose of radiation) and treatment group II (exposed to a 0.32 mSv dose of radiation). These subjects were subsequently sacrificed on the third and fifth days after treatment. Thereafter, histopathological examination was performed to identify any changes in the number of macrophages and lymphocytes. Results: The results of an HSD test confirmed that, on the third day, there were significant differences in the number of lymphocytes between the control group and treatment group I, as well as between the control group and treatment group II. On the fifth day, there were also significant differences in the number of lymphocytes between the control group and treatment group I, as well as between treatment group I and treatment group II. Similarly, there was a significant difference in the number of macrophage cells on the third day between the control group and treatment group I. On the fifth day, there were also significant differences in the number of macrophage cells between the control group and treatment group I, as well as between treatment group I and treatment group II. Conclusion: Dental x-ray exposure at a dose of 0.16 mSv can elevate the number of macrophages and lymphocytes on the third and fifth days. On the other hand, dental x-ray radiation at a dose of 0.32 mSv can reduce the number of macrophages on day 3 as well as the number of lymphocytes on the third and fifth days.